Predictors of Clostridium difficile infections in hospitalized children. Issue 2 (17th December 2013) - Samady, Waheeda; Bush, Ruth; Pong, Alice; Andrews, Allyson; Fisher, Erin Stucky
<x xml:space="preserve">Abstract</x> BACKGROUND Recent studies report an increasing incidence of Clostridium difficile infections (CDIs) in children and suggest that CDIs may occur outside known populations at risk. OBJECTIVE To identify clinical factors associated with CDI in a hospitalized pediatric population. METHODS A retrospective case‐control study was conducted with C difficile cases (CD) and controls (CTLs) in hospitalized children over a 2‐year period. CDs (N = 134) and 2:1 age‐matched CTLs (N = 274) with diarrheal illness were evaluated. RESULTS CDs and CTLs were similar in gender and race. Watery diarrhea was the most common type of diarrhea in CDs and CTLs. Immunodeficiency (46% vs 6%; P < 0.001), gastrointestinal (GI) disease (31% vs 18%; P = 0.005), and proton pump inhibitor (PPI) use (22% vs 7%; P < 0.001) were more frequent in CDs. Of CDs, 30% were defined as community acquired. Bloody diarrhea was more frequent in community‐acquired CD (28% vs 4% P < 0.001); however, other clinical variables were not statistically different. No antibiotic exposure, recent hospitalization, prolonged hospitalization, or past history of CDI existed in 8% of CDs. Multivariate logistic regression demonstrated that antibiotic use (odds ratio [OR]: 2.80, P = 0.001), recent hospitalization (OR: 2.33, P = 0.007), and immunodeficiency (OR: 6.02, P < 0.001) were significantly associated with cases when controlling for PPI use, having GI disease, and history of abdominal surgery. CONCLUSIONS Clinical history is of greater value than symptoms in distinguishing CD, with immunodeficiency having the strongest association. An important percentage of CDs did not have any risk factors, confirming concerns that CDIs do occur in otherwise low‐risk pediatric populations Journal of Hospital Medicine 2014;9:94–98. © 2013 Society of Hospital Medicine